(untitled) (Eurasian Journal of Ecology, 2023)
Ecologic and geochemical assessment of the territory of Pavlodar region, influenced by natural and anthropogenic factors of environment, is conducted in the article. Salt deposits of drinking water are proposed to be used as indicative environment. The research method is the instrumental neutron activation analysis of limescale samples, conducted in Tomsk Polytechnic University. Content of rare earth elements (La, Ce, Sm, Eu, Tb, Yb, Lu) is assessed, and elemental ratio (La/Ce, La/Yb, La+Ce/Sm+Eu, La+Ce/Yb+Lu) in salt deposits of drinking water of Pavlodar region is defined. Schematic maps of distribution of rare earth elements in salt deposits of drinking water of Pavlodar region, which demonstrate preferential accumulation in the northern part of the region, were constructed. The source of the given elements is of a natural and athropogenic genesis, caused by location of titanium-zirconium deposits in this part of region. Ratio of light lanthanides to heavy lanthanides demonstrates that salt deposits of drinking water of the research territory tends to light lanthanides, except for the limescale of Baynaul, Sharbakty, Aktogay districts. Ratio of the sum of rare earth elements to radioactive elements demonstrates that limescale is preferentially characterized as with high content of uranium, except for the salt deposits of drinking water from Irtyshsk district. Key words: rare earth elements, geochemistry, limescale, Pavlodar region.